Maximin Play in Two-Person Bimatrix Games - Vitaly Pruzhansky (Tinbergen Institute, 2003)
Since the seminal paper of Nash (1950) game theoretic literature has focused mostly on equilibrium and not on maximin (minimax) strategies. We study the properties of these strategies in 2-player non-zero-sum strategic games, whose Nash equilibria are only mixed.
Keywords: C72; 330; Non-cooperative games; Spieltheorie